Reduction in acute filariasis morbidity during a mass drug administration trial to eliminate lymphatic filariasis in papua new guinea - Tisch, D.; Alexander, N.; Kiniboro, B.; Dagoro, H.; Siba, P.; Bockarie, M.; Alpers, Michael Philip; Kazura, J. (2011)
Background: Acute painful swelling of the extremities and scrotum are debilitating clinical manifestations of Wuchereria bancrofti infection. The ongoing global program to eliminate filariasis using mass drug administration is expected to decrease this and other forms of filarial morbidity in the future by preventing establishment of new infections as a consequence of eliminating transmission by the mosquito vector. We examined whether mass treatment with anti-filarial drugs has a more immediate health benefit by monitoring acute filariasis morbidity in Papua New Guinean communities that participated in a 5-year mass drug administration trial. Methodology/Principal Findings: Weekly active surveillance for acute filariasis morbidity defined by painful swelling of the extremities, scrotum and breast was performed 1 year before and each year after 4 annual mass administrations of anti-filarial drugs (16,480 person-years of observation). Acute morbidity events lasted <3 weeks in 92% of affected individuals and primarily involved the leg (74-79% of all annual events). The incidence for all communities considered together decreased from 0.39 per person-year in the pre-treatment year to 0.31, 0.15, 0.19 and 0.20 after each of 4 annual treatments (p<0.0001). Residents of communities with high pre-treatment transmission intensities (224-742 infective bites/person/year) experienced a greater reduction in acute morbidity (0.62 episodes per person-year pre-treatment vs. 0.30 in the 4th post-treatment year) than residents of communities with moderate pre-treatment transmission intensities (24-167 infective bites/person/year; 0.28 episodes per person-year pre-treatment vs. 0.16 in the 4th post-treatment year). Conclusions: Mass administration of anti-filarial drugs results in immediate health benefit by decreasing the incidence of acute attacks of leg and arm swelling in people with pre-existing infection. Reduction in acute filariasis morbidity parallels decreased transmission intensity, suggesting that continuing exposure to infective mosquitoes is involved in the pathogenesis of acute filariasis morbidity. © 2011 Tisch et al.